2023
DOI: 10.1088/1748-3190/ad0aa9
|View full text |Cite
|
Sign up to set email alerts
|

Trailing-edge fringes enable robust aerodynamic force production and noise suppression in an owl wing model

Jiaxin Rong,
Yajun Jiang,
Yuta Murayama
et al.

Abstract: As one of the unique owl-wing morphologies, trailing-edge (TE) fringes are believed to play a critical role in the silent flight of owls and have been widely investigated using idealized single/tandem airfoils. However, the effect of TE fringes and associated mechanisms on the aeroacoustics of owl wings, which feature curved leading edges, wavy TEs, and several feather slots at the wingtips, have not yet been addressed. In this study, we constructed two 3D owl wing models, one with and one without TE fringes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Serrated trailing-edges have been widely studied in various fields. More recently, two 3D owl wing models, one with and one without trailing-edge fringes based on the geometric characteristics of a real owl wing, were constructed by Rong et al [20]; the large-eddy simulations and the Ffowcs Williams-Hawkings analogy were combined to resolve the aeroacoustic characteristics of the wing models. The results showed that the fringes on owl wings can robustly suppress aerodynamic noise while sustaining an aerodynamic performance comparable to that of a clean wing.…”
Section: Introductionmentioning
confidence: 99%
“…Serrated trailing-edges have been widely studied in various fields. More recently, two 3D owl wing models, one with and one without trailing-edge fringes based on the geometric characteristics of a real owl wing, were constructed by Rong et al [20]; the large-eddy simulations and the Ffowcs Williams-Hawkings analogy were combined to resolve the aeroacoustic characteristics of the wing models. The results showed that the fringes on owl wings can robustly suppress aerodynamic noise while sustaining an aerodynamic performance comparable to that of a clean wing.…”
Section: Introductionmentioning
confidence: 99%